Variabilidade genética de subpopulações de Mauritia flexuosa L.f (Arecaceae) em veredas do Estado de Goiás - Corrêa, Kássia Marques (2014)
Mauritia flexuosa is a large palm tree, commonly known as buriti that has wide distribution in the Cerrado, especially in association with fountains of waters and wetlands in formations known as palm swamps. The genetic variability of a species allows to elucidate the role of evolutionary processes in populations, contributing to the definition of efficient strategies for their use and conservation. Microsatellite markers are useful to quantify the level of variability among and within subpopulations. This study aimed to evaluate the genetic variability of six subpopulations of Mauritia flexuosa located in conserved and disturbed state of Goiás paths, based on microsatellite markers. 175 individuals were evaluated from six subpopulations. Genomic DNA was extracted from leaf tissue and subsequently quantified and diluted for performing polymerase chain reactions, using ten microsatellite loci. It was used an ABI3500 automatic sequencer, which acts through a capillary electrophoresis system, from which the genotypes were obtained. The array of genotypes obtained was used to estimate genetic diversity parameters among and within subpopulções. The analyzes were performed using GDA software. The average number of alleles per locus in subpopulations was 6,2, ranging from 5,6 to 7,0. The values of expected (He) and observed (Ho) heterozygosity were equal to 0,645 and 0,659, respectively, showing Ho value close to that expected by Hardy-Weinberg equilibrium. The analysis of population genetic structure revealed that subpopulations of M. flexuosa are moderately structured with θ = 0,099. The estimated value for f was not significant, as expected for dioecious species. The total fixation index considering all subpopulations was F = 0,08 , very close to the value of θ. This suggests that the genetic structure observed in these subpopulations is related to an effect of drifting associated with some restriction to gene flow between subpopulations. The limitation of gene flow between M. flexuosa subpopulations can be associated with the environment in which they occur, because the palm swamps have disjunct distributions and areas of dry land around them can act as barriers to gene flow. Another factor that could be related to this restriction to gene flow is the dispersion of seeds by zoochory, which becomes 13 difficult in fragmented environments and impracticable if it is kept in place unfavorable for seed germination. It was concluded that the sampled subpopulations showed a low level of inbreeding, and a relatively high genetic diversity. There is significant genetic structure, probably due to a slight isolation between subpopulations associated with the effects of genetic drift within subpopulations.